A Sustainable Method for Removal of the Full Range of Liquid and Solid Hydrocarbons from Water Including Up- and Recycling - Gaß, Henrik; Sarcletti, Marco; Müller, Lukas; Hübner, Sabine; Yokosawa, Tadahiro; Park, Hyoungwon; Przybilla, Thomas; Spiecker, Erdmann; Halik, Marcus (Advanced Science, 2023)
Beyond their CO2 emittance when burned as fuels, hydrocarbons (HCs) serve as omnipresent raw materials and commodities. No matter if as liquid oil spills or the endless amounts of plastic roaming the oceans, HCs behave as persistent pollutants with water as main carrier to distribute. Even if their general chemical structure [-(CH2)n-] is quite simple, the endless range of n leads to contaminations of different appearances and properties. A water remediation method based on superparamagnetic iron oxide nanoparticles (SPIONs) modified with self-assembled monolayers of alkyl phosphonic acid derivatives is presented. These molecules enable the SPIONs to non-covalently bind HCs, independently from the molecular weight, size and morphology. The attractive interaction is mainly based on hydrophobic and Coulomb interaction, which allows recycling of the SPIONs. The superparamagnetic core allows a simple magnetic collection and separation from the water phase which makes it a promising addition to wastewater treatment. Agglomerates of collected plastic “waste” even exhibit superior adsorption properties for crude oil, another hydrocarbon waste which gives these collected wastes a second life. This upcycling approach combined with presented recycling methods enables a complete recycling loop.<br

Highly Efficient Encapsulation and Phase Separation of Apolar Molecules by Magnetic Shell‐by‐Shell‐Coated Nanocarriers in Water - Luchs, Tobias; Sarcletti, Marco; Zeininger, Lukas; Portilla Berlanga, Luis; Fischer, Christian; Harder, Sjoerd; Halik, Marcus; Hirsch, Andreas (Chemistry - A European Journal, 2018)
We report on the development of a supramolecular nanocarrier concept that allows for the encapsulation and separation of small apolar molecules from water. The nanocarriers consist of shell‐by‐shell‐coated nanoparticles such as TiO2 and ferromagnetic Fe3O4. The first ligand shell is provided by covalently bound hexadecyl phosphonic acid (PAC16) and the second shell by noncovalently assembled amphiphiles rendering the hybrid architecture soluble in water. Agitation of these constructs with water containing the hydrocarbons G1–G4, the fluorescent marker G5, the polychlorinated biphenyl PCB 77, or crude oil leads to a very efficient uptake (up to 411 %) of the apolar contaminant. In case of the hybrids containing a Fe3O4 core, straightforward phase separation by the action of an external magnet is provided. The load can easily be released by a final treatment with an organic solven
Keywords: hydrophobic molecules; nanocarriers; nanoparticles; noncovalent interactions; separation

Magnetic water cleaning - Halik, Marcus; Sarcletti, Marco; Zahn, Dirk (Nachrichten aus der Chemie, 2021)

Magnetite nanoparticles as efficient materials for removal of glyphosate from water - Park, Hyoungwon; May, Alexander; Portilla, Luis; Dietrich, Hanno; Münch, Friedrich; Rejek, Tobias; Sarcletti, Marco; Banspach, Leena; Zahn, Dirk; Halik, Marcus (Nature Sustainability, 2019)
Glyphosate is one of the most commonly used herbicides, but, due to its suspected toxicity, it is simultaneously the most disputed one. Its worldwide application in huge quantities may lead to water concentrations that locally exceed statutory contamination levels. Therefore, a simple toolkit is required to remove glyphosate and its major metabolite from water. Here we show a method for the magnetic remediation of glyphosate from artificial and real water samples to below the maximum permissible value or even below the analytical detection limit. The chemical structure of glyphosate enables fast and stable covalent binding on the surface of magnetite (Fe3O4) nanoparticles, which act as catchers and carriers for magnetic removal. The small size of the nanoparticles ( 20 nm diameter) provides a large active area. The glyphosate binding was analysed by infrared spectroscopy, thermogravimetric analysis and dynamic light scattering, while the remediation was investigated by liquid chromatography–mass spectrometry. Results from molecular dynamics simulations support the proposed binding mechanism. The combination of efficient remediation with inexpensive and recyclable magnetite nanoparticles suggests a simple method for the sustainable removal of glyphosate, and the concept may lead to a general approach to eliminate this class of organophosphorus compounds from water.
CRIS-Team Scopus Importer:2019-12-31

Non-substituted fused bis-tetracene based thin-film transistor with self-assembled monolayer hybrid dielectrics - Zhao, Baolin; Feofanov, Mikhail; Lungerich, Dominik; Park, Hyoungwon; Rejek, Tobias; Wittmann, Judith; Sarcletti, Marco; Amsharov, Konstantin; Halik, Marcus (Frontiers of Materials Science, 2020)
Polycyclic aromatic hydrocarbons with zigzag peripheries are high perspective candidates for organic electronics. However, large fused acenes are still poorly studied due to the tedious synthesis. Herein we report a non-substituted fused bistetracene DBATT (2.3,8.9-dibenzanthanthrene) as the semiconductor on low-voltage-driven organic thin-film transistors. The systematic studies of thin-film growth on various self-assembled monolayer (SAM) modified gate dielectrics and the electrical performances were carried out. The sub-monolayer of the semiconductor film shows larger island domains on the alkyl chain SAM. This device exhibits the hole mobility of 0.011 cm2·V−1·s−1 with a current ratio of IonIIoff above 105.
CRIS-Team Scopus Importer:2020-09-11
Keywords: contact resistance; fused bis-tetracene; organic field-effect transistor; self-assembled monolayer

Potent method of extracting glyphosate from water using superparamagnetic nanoparticles - Park, Hyoungwon; Sarcletti, Marco; Halik, Marcus (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2019)
CRIS-Team WoS Importer:2019-08-23

Remediation of charged organic pollutants—binding motifs for highly efficient water cleaning with nanoparticles - Eigen, Andreas; Schmidt, Victoria; Sarcletti, Marco; Freygang, Selina; Hartmann-Bausewein, Andreas; Schneider, Vanessa; Zehetmeier, Anna; Mauritz, Vincent; Müller, Lukas; Gaß, Henrik; Rockmann, Linda; Crisp, Ryan; et al. (Nano Select, 2023)
Many charged organic molecules behave as persistent and hazardous pollutants with harmful effects on human health and ecosystems. They are widely distributed related to their charged molecular structure that provides water solubility. In order to track the fate and behavior of such pollutants, charged dyes with specific absorption in the visible spectra serve as convenient model compounds. We provide a platform of smart adsorbers that efficiently remediate positively and negatively charged dyes (crystal violet and Amaranth) from water. Metal oxide nanoparticles serve as a core with an intrinsically large surface area. The surface potential was tuned towards positive or negative by decorating the cores with self-assembled monolayers of dedicated long-chained phosphonic acid derivatives. Selective remediation of the dyes was obtained with corresponding oppositely charged core-shell nanoparticles. Mixed dye solution can be cleaned by a cascade approach or by applying both particle systems simultaneously. The removal efficiency was determined as a function of particle concentration via UV-spectroscopy. The results of remediation experiments at different pH values and using superparamagnetic iron oxide nanoparticle cores lead to a simple process with recycling capabilit

Superoleophilic Magnetic Iron Oxide Nanoparticles for Effective Hydrocarbon Removal from Water - Sarcletti, Marco; Vivod, Dustin; Luchs, Tobias; Rejek, Tobias; Portilla Berlanga, Luis; Müller, Lukas; Dietrich, Hanno; Hirsch, Andreas; Zahn, Dirk; Halik, Marcus (Advanced Functional Materials, 2019)
Various hydrocarbons are efficiently extracted from water by using a new sorbent material based on covalently functionalized magnetic nanoparticles. The functionalization of the magnetite nanoparticles with a self‐assembled monolayer of hexadecylphosphonic acid renders the nanoparticles oleophilic and the magnetic nature of magnetite allows for simple extraction of the hydrocarbon‐soaked sorbent. The sorbent material is capable of extracting single contaminants such as alkanes and aromatics and complex hydrocarbon mixtures such as crude oils in high extraction rates of up to 14 times the sorbent volume. Experimental results are explained by molecular dynamics simulations on the adsorption of single components from a hydrocarbon‐water mixture to the alkylphosphonic acid layer on the nanoparticles. The core–shell sorbent material is highly stable and therefore, reusable over several successive extraction cycles without degradation. The extraction performance is determined at different water temperatures, different water sources, and different magnetic core materials and evaluated compared to heptadecanoic acid functionalized magnetite. The new sorbent material provides the opportunity for an efficient, reliable, inexpensive, and environmental friendly removal of hydrocarbons from wate
Keywords: magnetic nanoparticles; functionalized nanoparticles; oil extraction; water remediation; phosphonic acids

The mutual influence of surface energy and substrate temperature on the saturation mobility in organic semiconductors - Sarcletti, Marco; Schmaltz, Thomas; Halik, Marcus (Organic Electronics, 2014)
We report on a mutual correlation between the substrate temperature during semiconductor deposition and the surface energy of the gate dielectric on the charge carrier mobility in bottom gate top contact organic field effect transistors (OFETs) with N,N′-diphenyl-3,4,9,10-perylene tetracarboxylic diimide (DP-PDI) as organic semiconductor. The gate dielectric consists of a thin gate aluminum oxide and a self-assembled monolayer (SAM) with which the surface energy of the hybrid dielectric is tuned. The substrate temperature during evaporation of the DP-PDI semiconductor was systematically varied to obtain the best charge carrier mobility for each SAM. We found that the optimum substrate temperature correlates with the surface energy. Devices with low surface energy reach best mobility at higher substrate temperatures than devices with a higher surface energy.

The remediation of nano-/microplastics from water - Sarcletti, Marco; Park, Hyoungwon; Wirth, Janis; Englisch, Silvan; Eigen, Andreas; Drobek, Dominik; Vivod, Dustin; Friedrich, Bernhard; Tietze, Rainer; Alexiou, Christoph; Zahn, Dirk; Apeleo Zubiri, Benjamin; et al. (Materials Today, 2021)
Nano-/microplastics (NP) is a human-made emerging contaminant with worldwide occurrence. The small size (below one micrometer), the different chemical nature and the persistence make NP to potential hazards with suspect probability of tissue penetration and inflammation or as accumulator for toxins. A strategy to stop the spill of novel NP is the remediation from waste water or rivers as prominent distributors. We have developed core–shell superparamagnetic iron oxide nanoparticles (SPIONs) that attract NP and glue them to larger agglomerates which then can be removed from water by applying an external magnetic field. The shell molecules provide two interaction motifs towards NP. The tuned surface potential of the functionalized SPIONs attract complementary charged NP efficiently and the n-alkyl chain is dedicated to preferential interaction towards organic NP rather than inorganic particles. Structural analytics and molecular dynamics simulation support the proposed concept. Systematic remediation experiments with different NP (chemical structures, sizes and mixtures), from different waters – including river water – and with different SPION core materials indicate a universal validity of the concept, with best remediation performance for mixed NP. We suggest a method for broadband remediation of various NP with simple materials and processes, which both have the potential to be up-scaled.<br

Tunable Composition of Mixed Self-Assembled Shell-by-Shell Structures on Nanoparticle Surfaces - Eigen, Andreas; Stiegler, Lisa; Gradl, Susanne; Schneider, Vanessa; Wedler, Vincent; Gaß, Henrik; Müller, Lukas; Sarcletti, Marco; Heinrich, Markus; Hirsch, Andreas; Halik, Marcus (Advanced Materials Interfaces, 2022)
The formation of mixed shell-by-shell (SbS) systems with tunable shell compositions is demonstrated by using molecular self-assembly driven by chemical recognition motifs. Aluminum oxide nanoparticles (AlOx-NPs) act as template surface for a self-assembled monolayer (SAM) of either partially fluorinated fluoroalkyl or alkyl chained phosphonic acid derivatives or defined stoichiometric mixtures of those. By providing an equimolar mixture of corresponding fluoroalkyl and alkyl-chained amphiphiles in water, the stoichiometry of underlaying mixed SAM on the NP-surface preferentially directs the composition of the secondary self-assembly. The composition of the shell-by-shell assemblies is studied by high performance liquid chromatography and fluorescence spectroscopy. The concept allows the formation of NP-templated vesicle-like bilayer structures, even consisting of orthogonal chain structures in tunable composition driven by chemical recognition and hydrophobic segregation.
Created from Fastlane, Scopus look-up
Keywords: hydro-; fluoro-; lipophilic/phobic; nanoparticles; self-assembly; shell-by-shell architectures; surface chemistry

Use of oleophilic magnetite nanoparticles as efficient sorbent for water contaminants - Sarcletti, Marco; Vivod, Dustin; Luchs, Tobias; Rejek, Tobias; Portilla, Luis; Hirsch, Andreas; Zahn, Dirk; Halik, Marcus (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2019)
CRIS-Team WoS Importer:2019-08-23

Wafer-Scale Organic Complementary Inverters Fabricated with Self-Assembled Monolayer Field-Effect Transistors - Zhao, Baolin; Gothe, Bastian; Sarcletti, Marco; Zhao, Yuhan; Rejek, Tobias; Liu, Xinxin; Park, Hyoungwon; Strohriegl, Peter; Halik, Marcus (Advanced Electronic Materials, 2020)
Self-assembled monolayers (SAMs) of π-conjugated molecules can achieve robust charge transport by the formation of ordered 2D layers at the desired regions, which enable their application for organic integrated circuits. Here, the self-assembled monolayer field-effect transistor concept is applied as a scalable method to realize fully integrated complementary inverters by stepwise semiconductor deposition. Two-component stacked bilayer ambipolar transistors are fabricated by semiconducting self-assembled monolayers (n-SAM or p-SAM) as the bottom layer and a complementary thin-film semiconductor layer on top. The integrated complementary metal-oxide-semiconductor like (CMOS-like) inverter achieves proper logic performances. The nanometer-thin monolayers exhibit effective charge transport and their flat, homogeneous surfaces benefit the interconnected growth of the top layer. Furthermore, by controlling the solution-based and region-selective deposition of p- and n-type SAMs, fully integrated CMOS inverters are realized on wafer scale by photolithography for the first time. The CMOS inverters show a nearly 100% yield with a gain up to 48, and noise margin 3.68 V (73.6% of VDD/2). The strategy of semiconducting SAMs for digital logic gates demonstrates a reliable approach for sophisticated large-area circuits.
CRIS-Team Scopus Importer:2020-08-14
Keywords: organic complementary metal-oxide-semiconductor inverters; organic field-effect transistors; p-n heterojunction structures; self-assembled monolayers